2021
DOI: 10.3329/sja.v18i2.51114
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Soybean Meal by Shrimp Head Meal (Penaeus Monodon) in Poultry Ration for the Performance of Growing Pullets

Abstract: To minimize the production cost of poultry and poultry products, it is important to formulate low cost balanced ration utilizing unconventional feed resources. Therefore, the experiment was carried out to measure the effect of substituting soybean meal (SBM) by different levels of shrimp head meal (SHM) to the ration of growing layer pullets. A control corn-soybean layer grower (pullet) diet and four different levels of SHM included diets as substitution of SBMwere fed to five groups of Hisex White pullets fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The decline in the growth performance of the turkeys as the level of SWM increased in the diets could be attributed to the reduced nutritional profile of SWM compared to FM (Oduguwa et al, 2004). The present finding is in line with the report of Ingweye et al (2008) and Islam et al (2020). They reported decline in growth indices when SWM substituted FM in the diets of broiler chickens.…”
Section: Blood Indicessupporting
confidence: 93%
See 1 more Smart Citation
“…The decline in the growth performance of the turkeys as the level of SWM increased in the diets could be attributed to the reduced nutritional profile of SWM compared to FM (Oduguwa et al, 2004). The present finding is in line with the report of Ingweye et al (2008) and Islam et al (2020). They reported decline in growth indices when SWM substituted FM in the diets of broiler chickens.…”
Section: Blood Indicessupporting
confidence: 93%
“…The results of this study contradicted the findings of Okoye et al (2005) who reported a reduced feed intake when FM was substituted with SWM in the diets of broiler chickens. On their part, Islam et al, (2020) reported significant difference in cumulative feed intake among different treatment means from 5th to 18th weeks of age when pullet chickens were fed SWM in replacement for SBM. The numerical increase in the values of FCR and decrease in the values of PER as the level of SWM increased in the diets could be attributed to the superiority of FM to SWM in terms of nutrients content (Oduguwa et al, 2004) The result of cost of producing turkey on different diets is in line with the result of Aktar et al (2011).…”
Section: Blood Indicesmentioning
confidence: 99%
“…Previous research on the utilisation of SWM has focused on broilers (Rahman and Koh 2016;Rahman, 2016), growing pullets (Islam et al, 2020), and pigs (Yugandharkumar et al, 2017). However, to the best of our knowledge, there is paucity of information on utilisation of SWM in rations for turkeys.…”
Section: Introductionmentioning
confidence: 99%